2019
DOI: 10.1002/open.201800296
|View full text |Cite
|
Sign up to set email alerts
|

Bimolecular Cross‐Metathesis of a Tetrasubstituted Alkene with Allylic Sulfones

Abstract: Exquisite control of catalytic metathesis reactivity is possible through ligand‐based variation of ruthenium carbene complexes. Sterically hindered alkenes, however, remain a generally recalcitrant class of substrates for intermolecular cross‐metathesis. Allylic chalcogenides (sulfides and selenides) have emerged as “privileged” substrates that exhibit enhanced turnover rates with the commercially available second‐generation ruthenium catalyst. Increased turnover rates are advantageous when competing catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…To commence our investigations enantiopure epoxide 2 , as a relay-actuated Δ 6,7 -functionalized monoterpenoid derivative, was prepared from diol 1 using the method of Corey et al (Scheme ). Using our previously identified conditions (10 mol % ruthenium benzylidene precatalyst 5 , alkene [5 equiv], 50 °C, 1 h), attempted relay cross metathesis reaction between epoxide 2 and citral ( 3 ) , to give C 15 -sesquiterpenoid 4 using 5 was unsuccessful (Table , entry 1). Further attempts with 10 equiv of 3 (entry 2) or at room temperature (entry 3) or with 2 mol % catalyst loading (entry 4) also failed.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…To commence our investigations enantiopure epoxide 2 , as a relay-actuated Δ 6,7 -functionalized monoterpenoid derivative, was prepared from diol 1 using the method of Corey et al (Scheme ). Using our previously identified conditions (10 mol % ruthenium benzylidene precatalyst 5 , alkene [5 equiv], 50 °C, 1 h), attempted relay cross metathesis reaction between epoxide 2 and citral ( 3 ) , to give C 15 -sesquiterpenoid 4 using 5 was unsuccessful (Table , entry 1). Further attempts with 10 equiv of 3 (entry 2) or at room temperature (entry 3) or with 2 mol % catalyst loading (entry 4) also failed.…”
supporting
confidence: 63%
“…3:1 at the newly formed olefin (Δ 6,7 ) and as ca. 2−3:1 at the α,βunsaturated aldehyde by 1 H NMR and assigned on the basis of characteristic 13 C NMR shielded methyl resonances for E-isomers (see the Supporting Information). c Purification not attempted due to complex mixtures of products.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ene revealed that both regioselectivities could be obtained depending on the nature of the catalyst [30]. The cross-metathesis of a sterically hindered vinylheterocyclic substrate with 2-methylbut-2-ene in the presence of the catalyst Ru2 yielded a mixture of the two regioisomers in a disubstituted/trisubstituted double bond ratio of 2.4/1.0 [31]. The regioselectivity leading to the formation of a 1,2-disubstituted double bond is also exemplified by the cross metathesis of 2-methylbut-2-ene with n-butyl acrylate in which the trans-n-butyl crotonate was formed in 83% yield [26] due to the higher reactivity of the alkene than the acrylate to generate a ruthenium ethylidene species, as also observed under stoichiometric conditions from the first generation cyclohexyl ester ruthenium carbene RuCl2(PCy3)2(=CHCO2Cy) and 2-methyl-1pentene [32].…”
Section: Revised Manuscriptmentioning
confidence: 99%
“…[31][32][33] An alternative compound for introducing prenyl groups by alkene cross-metathesis reactions without low temperature or pressure regulation requirements would be the highly symmetric alkene 2,3-dimethyl-2-butene (Figure 1, top middle) which, however, it is difficult to find as a reactant in any reported metathesis reaction. [34,35] This can be due to its fully tetrasubstituted alkene structure, which severely hampers the initial formation of the intermediate metal carbene complex. [36] We will confirm in this work the unreactivity of this alkene under standard alkene metathesis conditions (see ahead).…”
Section: Introductionmentioning
confidence: 99%